Orthographic Influences When Processing Spoken Pseudowords: Theoretical Implications - Taft, Marcus (Frontiers in Psychology, 2011)
When we hear an utterance, is the orthographic representation of that utterance activated when it is being processed? Orthographic influences have been previously examined in relation to spoken pseudoword processing in three different paradigms. Unlike real word processing, no orthographic effects with pseudowords have been observed in a phoneme goodness ratings task, and there is a mixed outcome in studies looking for spelling-sound consistency effects. In contrast, the orthography of spoken pseudohomographs has been shown to be activated, given that they prime their homographic base-word. Explanations are sought for the findings in these three paradigms, leading to an exploration of theoretical models of spoken word recognition.